Market Structure and Audit Fees: A Local Analysis* - BANDYOPADHYAY, SATI P.; KAO, JENNIFER L. (Contemporary Accounting Research, 2004)
Abstract This study conducts a local analysis of the relation between market structure and audit fees. The research question of interest to us is how audit fees are determined by each practicing local office, after taking into account the auditor's own position in a local market and the influence exerted by his or her clients. Appealing to the economic theories of monopoly and monopsony power, we hypothesize a positive audit fee‐concentration relation, and a negative audit fee‐client influence relation. Results indicate that auditor market concentration is positively associated with the non‐Big 6 audit fees but is unrelated to the Big 6 audit fees. Evidence is mixed concerning the client influence hypothesis. When this construct is proxied by the number of rival auditors operating within a geographic area centered on the municipality, the prediction of negative audit fee‐client influence relation is strongly supported for both groups of auditors. Results are much weaker using measures developed based on the relative importance of a municipal client to its auditor's audit portfolio. The issues addressed in this study are important at a time when the Canadian municipal sector is undergoing major changes because of municipal amalgamation, altering the underlying market structure for audit services and the bargaining position of a municipality vis‐Ã‐vis its auditor. More broadly speaking, our analysis implies that when assessing an auditor's report for signs of client pressure, the professional oversight bodies and regulatory authorities need to consider the relative, rather than the absolute, bargaining position of the client in question.